2016
DOI: 10.1088/0953-2048/29/10/105019
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and superconducting properties of internal Mg diffusion processed MgB2wires using MgB4precursors

Abstract: Monofilament MgB2/Nb/Monel wires were fabricated using three different MgB4 precursors by an internal Mg diffusion (IMD) process. The wire geometry and heat-treatment conditions were optimized in order to improve the critical current density (Jc) of the MgB2 wire. The influences of the quality of MgB4 powders, such as the particle size and MgO impurity, on the microstructure and superconducting properties of the wires were discussed. Although there were small amounts of voids, unreacted MgB4 particles and MgO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Therefore, we concluded that adding MgB 4 externally is a safer way to get the best performance than producing it in situ. Several researchers created MgB 4 employing a diffusion technique . In this work, we tried to synthesize MgB 4 separately and sinter its tiny amounts together with the MgB 2 powder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we concluded that adding MgB 4 externally is a safer way to get the best performance than producing it in situ. Several researchers created MgB 4 employing a diffusion technique . In this work, we tried to synthesize MgB 4 separately and sinter its tiny amounts together with the MgB 2 powder.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers created MgB 4 employing a diffusion technique. [14][15][16][17][18] In this work, we tried to synthesize MgB 4 separately and sinter its tiny amounts together with the MgB 2 powder. Here, pinning performance of such a MgB 2 bulk composite is discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, other techniques have been developed to try to increase the density of the MgB 2 [1][2][3]. Among them, the internal magnesium diffusion (IMD) technique was successfully employed, resulting in wires with an increased critical current density, J c , in the superconducting layers [4][5][6].…”
Section: Introductionmentioning
confidence: 99%